Single tracheal inoculation of Aspergillus fumigatus conidia induced aspergillosis in juvenile falcons (Falco spp.). Issue 1 (2nd January 2018) - Fischer, Dominik; Van Waeyenberghe, Lieven; Failing, Klaus; Martel, An; Lierz, Michael
ABSTRACT: Aspergillosis is a common and life-threatening respiratory disease in raptors with acute and chronic courses. Among raptors, gyrfalcons ( Falco rusticolus ) and their hybrids are often declared to be highly susceptible with juvenile individuals being the most susceptible. However, species- and age-specific experimental studies are lacking and minimal infective doses (IDs) for Aspergillus spp. conidia are unknown.Therefore, 8-week-old, healthy gyr-hybrid falcons ( F. rusticolus X F. cherrug ) ( N = 18) were experimentally infected with Aspergillus fumigatus using a single intratracheal inoculation with varying dosages of conidia (10 2 to 10 7 conidia). Over 28 days, clinical signs were monitored as well as haematological and serological parameters. Following euthanasia, necropsy, histopathology, bacteriology, and mycology were performed. Re-isolated fungi were compared to the inoculum using microsatellite length polymorphisms. During the trial, clinical signs and dyspnoea correlated significantly with the ID. Necropsy revealed fungal lesions in the upper and lower airways of 10/18 inoculated falcons, but not in the control birds. In 9/18 inoculated falcons, fungal granulomas were confirmed in histopathology and A. fumigatus was re-isolated from these granulomas. Except one nasal isolate all re-isolated fungal strains were identical to the inoculum strain. Based on mycology and histopathology a minimal ID of 50% was calculated to be MID50% (±S.E.) = 10 4.52±0.67 for a single tracheal inoculation of A. fumigatus conidia. This study demonstrates for the first time that a single exposure is able to cause acute aspergillosis in juvenile falcons.